2016
DOI: 10.1111/aab.12280
|View full text |Cite
|
Sign up to set email alerts
|

Importance of DNA and histone methylation in in vitro plant propagation for crop improvement: a review

Abstract: Epigenetic changes including DNA and histone methylation may reorganise the nuclear architecture during in vitro culture. The states of methylation resulting from in vitro cultures are often related to control the somatic embryogenesis and regeneration process via modulating gene expression. By changing the methylation profile, it is possible to alter gene expression which may be applicable to produce large number of high quality planting materials or to improve agronomic traits leading to crop improvement. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 125 publications
(159 reference statements)
0
18
0
Order By: Relevance
“…Increasing knowledge of the induction of SE and of the development of somatic embryos will lead to the development of multiple biotechnological applications and new opportunities for the understanding of the fundamental aspects of SE. In particular, the alteration in the methylation or acetylation profile of DNA and/or histones by genome-editing techniques holds great promise to increase the production and to improve the quality of crops of agronomical importance (Karim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing knowledge of the induction of SE and of the development of somatic embryos will lead to the development of multiple biotechnological applications and new opportunities for the understanding of the fundamental aspects of SE. In particular, the alteration in the methylation or acetylation profile of DNA and/or histones by genome-editing techniques holds great promise to increase the production and to improve the quality of crops of agronomical importance (Karim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…All these modifications have also been observed during in vitro culture establishment, being the major source of somaclonal variation between cultures . It is therefore not surprising that cell lines subcultured over long periods of time in optimal conditions can adapt their physiology to long‐term cultivation in in vitro conditions, similar to the response of complete plants to environmental changes.…”
Section: Yield Loss During Long‐term In Vitro Maintenancementioning
confidence: 99%
“…Several studies have reported variable patterns in genomic methylation among genetically identical individual plants kept under different stress conditions. Interestingly, these specific patterns, known as epigenetic alleles or epialleles, can remain stable for several generations by inheritance .…”
Section: Yield Loss During Long‐term In Vitro Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Methylation states in the DNA, resulting from in vitro cultures, are often related to the control of SE and the regeneration process through the modulation of gene expression [ 19 , 23 ]. By changing the methylation profile, it is possible to alter gene expression, and this can be applied to produce a large number of high-quality plants or to improve the agronomic characteristics leading to the improvement of a crop [ 24 ]. By understanding how methylation alterations influence the acquisition of the developmental cell fate during in vitro cultures, we would be able to develop new strategies to enhance the embryogenic capability and totipotency in recalcitrant plant species and genotypes.…”
Section: Introductionmentioning
confidence: 99%